Blind Pouch Syndrome-associated Anastomotic Ulcer Diagnosed with Capsule and Double-balloon Endoscopy - Kubo, Kimitoshi (Intern Med, 2019)
Blind pouch syndrome-associated anastomotic ulcer is rare, and its endoscopic features remain poorly described. A 79-year-old man was referred to our hospital for melena. Capsule endoscopy revealed multiple ulcers in the small intestine. Double-balloon endoscopy (DBE) and a gastrografin examination through DBE revealed a potential anastomotic ulcer, a blind pouch, and a side-to-side anastomosis in the middle of the small intestine. Laparoscopic partial resection of the small intestine with anastomosis was performed on the suspected blind pouch syndrome-associated anastomotic ulcer. To our knowledge, this is the first report describing the endoscopic features of a blind pouch syndrome-associated anastomotic ulcer.